Imaging mass cytometry reveals the prominent role of myeloid cells at the maternal-fetal interface - Krop, Juliette; van der Zwan, Anita; Ijsselsteijn, Marieke E.; Kapsenberg, Hanneke; Luk, Sietse J.; Hendriks, Sanne H.; van der Keur, Carin; Verleng, Lotte J.; Somarakis, Antonis; van der Meeren, Lotte; Haasnoot, Geert; Bos, Manon; et al. (iScience, 2022)
Although the immunological complexity of the maternal-fetal interface is well appreciated, the actual interaction of maternal immune cells and fetal trophoblasts is insufficiently understood. To comprehend the composition and spatial orientation of maternal immune cells and fetal extravillous trophoblasts, we applied imaging mass cytometry on decidua basalis of the three trimesters of healthy pregnancy. Within all trimesters, we observed considerably higher frequencies of myeloid cells in the decidua than is seen with single-cell suspension techniques. Moreover, they were the most pronounced cell type in the microenvironment of other decidual cells. In first trimester, HLA-DR- macrophages represented the most abundant myeloid subcluster and these cells were frequently observed in the vicinity of trophoblasts. At term, HLA-DR+ macrophage subclusters were abundantly present and frequently observed in the microenvironment of T cells. Taken together, our results highlight the dynamic role of myeloid cells at the human maternal-fetal interface throughout gestation. [Display omitted] •Frequency of myeloid cells is underestimated after tissue digestion•Myeloid cells could support NK cells with proper trophoblast invasion•Myeloid cells are dynamic in their role throughout gestation Biological sciences; Immunology; Biotechnology; Biological sciences research methodologies